Morane AI et Dewoitine D. 530 : deux logiques de restauration pour une même finalité - Arnaud Mars (In Situ)
The French Air and Space museum at le Bourget houses two iconic aerobatic airplanes: a Morane AI and a Dewoitine 530. Between 2012 and 2016, these two airplanes were restored at the museum’s workshop, under the leadership of the author. Due to their very different initial conditions, they have been restored in two opposite ways: a minimum intervention on the Dewoitine and a ground-up restoration on the Morane. Through those projects, the author introduces the rich and complex work on museum aircraft. After presenting the specific characteristics of the artefacts, he describes the skills involved anf the execution of the job. Finally, using chosen past projects, he shares some experiences and possible evolutions in practice to be taken into consideration concerning the specificity of these incredible objects.